Visual Essay: Perspectives on Motherhood, Labour, and Emerging Technologies - Alzate, Catalina; Martínez, Angelica (Journal of the Motherhood Initiative for Research and Community Involvement, 2025)
This visual essay traces the concept of “full-time mother” proposed by Gillian Ranson in the first volume of this journal. It connects the concept to contemporary notions of motherhood, concerning how emerging technologies mediate the home and the workplace as prime contexts for mothering. In this visual essay, we think through images and symbols of work, technologies, and spaces using the means of collage and scan art while analyzing and critiquing the contemporary entanglement of motherhood and work, especially as digital technologies (re)produce the mandate that mothers need to excel both at home and at work. Moreover, through technological designs and narratives, we explore how excelling in those two realms is a measure and a standard for so-called good motherhood. The technologies studied and visually depicted include breast pumps, smart screens, and motherhood-related apps. Our visual and analytical exploration leads us to develop the concept of “prototypical motherhood,” a term that we use to refer to the performative role of motherhood as mixed with the dynamics of productive work, which points towards progress, efficiency, and economic growth. In this sense, mothers must work in specific ways to meet certain ideals, promises, and standards. Prototypical motherhood operates as the dispositif, in Foucauldian terms, to frame what is possible for mothers and what mothers are capable of and able to control, so they remain within the confines of the overlapping relationship of care and productive work. We conclude with design provocations to reimagine technology and motherhood, and how this discussion could be extended to the social structures where we live today.